A boy called Bat - Arnold, Elana K.; Santoso, Charles (New York : Walden Pond Press, an imprint of HarperCollinsPublishers, 2017)
When his veterinarian mom brings home a stray baby skunk that needs rehabilitation before it can be placed in a wild animal shelter, Bat, who has autism, resolves to prove that he is up to the challenge of caring for the skunk permanently.
Maine Student Book Award nominee 2018-2019.
Keywords: Autism -- Juvenile fiction; Skunks as pets -- Juvenile fiction; Wildlife rehabilitation -- Juvenile fiction